Takhrij and Syarah the Agrotechnology Hadith: Ingredients and Efficacy of Olives - Akmal Nur Fauzy; Wahyudin Darmalaksana; Agung Rahmadi (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the properties of the olive fruit. This research method is a qualitative type through literature study and field studies with the takhrij and syarah hadith approaches. The results and discussion of this research are the properties of olives recommended by the Prophet. The conclusion from the research of takhrij and syarah hadith regarding olives with the analysis of agro-technology studies shows that olives have nutritious ingredients for humans.